A case study on the performance comparison between mechanical grabber loader and semi-mechanised tractor for in field fresh fruit bunch collection / Mohamad Syafiq Ahmad - Ahmad, Mohamad Syafiq (Faculty of Plantation and Agrotechnology, 2016)
Malaysia is the second largest palm oil producer in the world. Despite oil palm industry is the fourth largest contributor to the national economy, this industry has been suffering from shortage of labour. Increasing land usage for the oil palm industry raises number of worker demand and increase the production cost. Thus, farm mechanization such as tractor mounted mechanical grabber loader with trailer is introduced for in-field collection and evacuation of FFB to reduce manpower dependency as well lowering the production cost. The data is measured and collected directly at the Johawaki Plantation estate in Lekir, Perak with the cooperation of the managing staff. This study compares the material capacity, effective field capacity and production cost between mechanical grabber loader and semi-mechanised tractor loader for in field FFB collection operation. Result indicates that material capacity, tonne per hour increased by 1.4 times with mechanical grabber loader compared to semi-mechanised tractor loader. Furthermore, the effective capacity of mechanical grabber is 2.56 hectare/hour which is higher compared to semi-mechanised tractor loader, 2 hectare/hour. Besides, the production cost, cost per tonne for mechanical loader system obtained is 2.5 fold lower than semi-mechanised tractor loader at the study site.